2017
DOI: 10.1515/acb-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Does Porcine Oocytes Maturation in Vitro is Regulated by Genes Involved in Transforming Growth Factor Beta Receptor Signaling Pathway?

Abstract: Summary:The oocyte growth and development in follicular environment are substantially accompanied by surrounding somatic cumulus (CCs) and granulosa cells (GCs). During these processes, the mammalian gametes reach full maturational stage and may be further successfully fertilized by single spermatozoon. These unique mechanisms are regulated by expression of clusters of genes and their biochemical signaling pathways. In this article we described differential expression pattern of transforming growth factor beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Moreover it was defined that proper regulation of these processes is required for complete maturation of oocytes. Our previous studies have shown various aspects of changes occurring in oocytes during maturation [1][2][3] and impact of environmental changes on these processes [4][5]. Morphological and biochemical alterations associated with the ability of embryo to formation of blood vessels networks seem to play pivotal role in successful implantation, decidualization and early embryo -maternal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it was defined that proper regulation of these processes is required for complete maturation of oocytes. Our previous studies have shown various aspects of changes occurring in oocytes during maturation [1][2][3] and impact of environmental changes on these processes [4][5]. Morphological and biochemical alterations associated with the ability of embryo to formation of blood vessels networks seem to play pivotal role in successful implantation, decidualization and early embryo -maternal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we introduced the primary culture systems based on: (1) human ovarian granulosa cells, (2) porcine ovarian granulosa cells, (3) porcine endometrial and myometrial cells, and (4) porcine epithelial oviductal cells (OECs) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…9, which these potential target genes are closely related to the oocyte development and follicle growth. It was also found that many targeting genes by these miRNAs mainly involved in TGF-beta related signaling pathway, which may play a significant role during early stages of porcine oocytes nuclear and cytoplasmic maturation, and these investigated transcripts may be also recommended as the markers of porcine oocytes with high capability in further embryo development 45,46 .…”
Section: Discussionmentioning
confidence: 99%